Associação entre escolaridade materna e prática de atividade física e comportamento sedentário em adolescentes brasileiros - Bruna Soares Faria (2018)
Introduction: Adolescence is a period of intense biological and social change and guidance on healthy habits and the modification of inappropriate practices at this stage is fundamental. Objective: To estimate the association between maternal schooling and practice of physical activity and sedentary behavior in Brazilian adolescents. Method: A cross-sectional study with data from the National School Health Survey, 2009, approved by the National Research Ethics Committee. We evaluated the students of the 9th year of elementary education in public and private schools of the 26 Brazilian capitals and the Federal District. The association between maternal schooling and the practice of physical activity and sedentary behavior was estimated through Poisson multiple regression, taking into account the hierarchical theoretical model for adjustment of confounding and mediators variables. A significance level of 5% was considered. Results: A total of 60,973 adolescents participated in the PeNSE, of which 54364 answered questions about physical activity and 58437 about sedentary behavior. Of these, 52.5% were female and 47.1% were 14 years old (minimum 11 and maximum 19 years). Adolescent children of mothers with complete higher education had a greater chance (PR: 1.16, 95% CI: 1.10-1.23) of practicing 300 minutes or more of total physical activity in the week compared to those who had unschooled mothers or incomplete elementary school. Adolescent children of mothers with complete primary education had a lower chance (PR: 0.77, 95% CI: 0.72-0.82) of practicing the recommended physical activity time for displacement, when compared to those whose mothers had the lowest instruction. Adolescent children of mothers with complete higher education had higher odds (RR: 1.08, 95% CI: 1.05-1.11) and (RR: 1.10, 95% CI: 1.01-1.19), of practicing the time of physical activity recommended for leisure as well as for physical activity in the school, respectively, when compared those whose mothers had the lowest level of schooling. Regarding sedentary behavior, children of mothers with higher education have a greater chance (RP: 1.04 95% CI: 1.02-1.06) of being less than 2 hours on screen to those with unschooled mothers. Conclusion: Higher levels of maternal schooling are associated with higher total physical activity and for domains (leisure and school) and with a high screen time in Brazilian adolescents living in the country 's capitals. However, much of this association is conditioned to individual factors, family support and behavioral. Thus, intervention is necessary in a comprehensive way, including both the adolescent as well as the environment in which he is inserted.